TINJAUAN MAQASHID AL-SYARIAH DALAM PRODUK iB HASANAH CARD PERBANKAN SYARIAH - iftiatul Farkhiyah; Sukamto (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
In the 21st century, the number of APMK (Card-BasedPayment Instruments) is increasing every year. Syariah Card inIndonesia has developed quite rapidly, this is influenced by thecontribution of the sharia card which cannot be underestimated in thewheels of the economy. This product can provide convenienceservices for cardholders such as cash shopping, zakat, insurance,mobile banking, electricity payments, PDAM through interest-freetransaction of sharia contracts. However, until now the existence of thesyariah card is still being debated by various parties because it hasnegative impacts including; 1) encourage customers to beconsumptive. 2) disrupt the main mission of Islamic banks inencouraging the creation of the real sector. 3) customers tend to delaybill payment. Apart from this, it is permissible for the sharia card to beable to create benefit goals that are in line with the content of Maqashidal-Syariah.This study uses a qualitative approach to the type of case studyresearch. The data sources used are primary data which includesdirect and secondary research through books, journals and otherauthorship articles. While the data collection procedure usedtriangulation techniques with multiple / source techniques. Based ondata analysis, it is concluded that BNI Syariah Malang Branch Officehas been running according to the applicable sharia principles.Besides the implementation of iB Hasanah card when viewed frommaqashid al-Sharia has met three tiers maqashid al-Sharia isdharuriyah, hajiyah and tahsiniyah